The Identity Transformation of David through Consumption in Une nouvelle amie - Lasman, Diah Kartini; Katim, Faiza Amara (Franconesia, 2025)
In modern society, consumption functions not only to fulfill material needs but also as a means of expression and identity formation, particularly in relation to gender. This study explores how gender identity transformation can occur through symbolic consumption. The film Une nouvelle amie (2014) by François Ozon serves as the corpus and is analyzed qualitatively through the narrative and cinematographic frameworks of Petrie & Boggs (2022) and Gustav Freytag’s Freytag Triangle (1863). Jean Baudrillard’s theory of consumerism (1970) is employed to examine how the consumption of symbolic objects by the protagonist contributes to identity construction. Additionally, Kathryn Woodward’s theory of identity (1997) is used to analyze how identity is formed through representation and social interaction. Findings reveal that symbolic consumption enables the character David to express femininity and construct a non-normative gender identity. Through engagement in inclusive social spaces and the consumption of gendered symbols, David constructs an identity outside traditional gender norms. This study highlights consumption not only as a visual signifier but also as an agentive medium in the construction of identity.